Consumer guilt predisposition in different generational cohorts - Silva, Filipa Barbosa Brito da (2022)
Purpose – Researchers and practitioners have become increasingly interested in emotions that greatly influence consumers’ behaviours, such as guilt. Guilt is a social emotion that impacts consumers’ decision-making process. Despite the growing attention given to this topic there are still gaps that can be filled regarding research into guilt. For example, it is yet to be defined how generational cohorts perceive and experience guilt feelings associated with consumption. Since companies’ have been forming different consumer segments to target individuals and meet their specific needs, analysing generational discrepancies regarding consumer guilt might bring useful insights for marketers. Hence, this research aims to understand if there are any differences in the way consumers who belong to different generational cohorts’ experience consumer guilt. Design/Method/approach - To investigate these topics, an online questionnaire was conducted. The data collected from 369 participants was analysed using the program IBM SPSS. Findings - The findings from this study revealed that there are differences in the way consumers of different generations experience guilt associated with consumption. From the six dimensions of guilt identified, it was possible to conclude that the older the generation to which consumers belong, the higher their tendency towards health guilt and social responsibility guilt. The results did not indicate that individuals from different generations have distinct predispositions to feel indulgence guilt, mistiming guilt, misevaluation guilt, or social influence guilt. Originality/value - In a world where understanding consumers’ behaviour is a growing concern for companies, this research contributes to the body of knowledge regarding guilt. The findings of this study provide useful insights for marketers particularly about different generations’ predisposition to feel consumer guilt.